Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Literasi Sains Pada Tema Pencemaran Lingkungan (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2022)
This article explains The Influence of Problem Based Learning Learning Models on Students' Scientific Literacy Ability on the Theme of Environmental Pollution". The research method used is a Quasi-Experimental Design with a non-equivalent control group design. Respondents in the study included 1 teacher and 22 students. The results of the pretest and posttest were used to collect data on students' scientific literacy abilities, which were then analyzed with the help of the SPSS 28 for Windows version program. The control class and the experimental class were found to be normally distributed and homogeneous after being tested using the normality and homogeneity tests. The independent t test was used in testing the hypothesis in this study. The results of the research show value a significance of 0.001 <0.05 indicates that H0 is rejected and H1 is accepted. It can be seen that the experimental class that applied the PBL model and the control class that used Discovery Learning had statistically significant different values. Based on data analysis, the PBL model influences students' scientific literacy skills on the theme of environmental pollution. Therefore, the authors suggest that teachers use the PBL model in teaching in class. Keywords : Problem Based Learning, Scientific Literacy , Environmental Pollution.